KOLEKSI REPOSITORI SEBAGAI SARANA DISEMINASI INFORMASI DI MASA PANDEMI: Studi Kasus di Perpustakaan UIN Sunan Ampel - Hary Supriyatno; Aries Hamidah (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2022)
This study aims to answer questions about the media used in information dissemination during the pandemic, the types of collections contained in the repository, and the level of utilization of repository collections during the pandemic at the Library of UIN Sunan Ampel. The method used in this research is descriptive qualitative, namely conducting an in-depth study of symptoms that occur in a certain place and time using observation and documentation techniques on the object of research, that is the library repository on the website http://digilib.uinsby.ac.id. The research findings are as follows: 1) the media used as a means of disseminating information at the UIN Sunan Ampel Library are subscription e-books, subscription journals, UINSA books, and repositories. 2) There are 4 types of collections available in the repository, namely final and non-final assignments. The final project consists of a thesis, a thesis, and a dissertation. Meanwhile, non-final digital collections include scientific papers, journal articles, mass media articles, articles in books, books, textbooks, conferences, KKN/PKL reports, research reports, service reports, papers, scientific orations, guidelines, and proceedings. 3) The utilization rate of repository collections has increased during the pandemic compared to before. This can be seen from the number of page loads which increased by 86%, unique visits increased by 34%, first time visits increased by 60%, and returning visits increased by 6%.